2007
DOI: 10.1016/j.jasms.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Top-down quantitation and characterization of SILAC-labeled proteins

Abstract: Stable isotope labeling by amino acids in cell culture (SILAC) has become a popular labeling strategy for peptide quantitation in proteomics experiments. If the SILAC technology could be extended to intact proteins, it would enable direct quantitation of their relative expression levels and of the degree of modification between different samples. Here we show through modeling and experiments that SILAC is suitable for intact protein quantitation and top-down characterization. When SILAC-labeling lysine and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 20 publications
1
72
0
Order By: Relevance
“…C 18 -and C 13 -labelled L-lysine) which is supplied in two living cell populations and becomes incorporated into all newly synthesised proteins upon rounds of cell division. This pioneer labelling strategy is utilised by numerous research groups in multiple pragmatic applications such as biomarker discovery [73], cell signalling dynamics [74], subcellular and interaction proteomics [75][76][77][78] and identification of post-translational modification sites [79,80]. Even though SILAC represents a robust labelling strategy, the existing algorithms of SILAC-dependent MS data analysis are incapable of handling complex data sets.…”
Section: Label-based Mass Spectrometrymentioning
confidence: 99%
“…C 18 -and C 13 -labelled L-lysine) which is supplied in two living cell populations and becomes incorporated into all newly synthesised proteins upon rounds of cell division. This pioneer labelling strategy is utilised by numerous research groups in multiple pragmatic applications such as biomarker discovery [73], cell signalling dynamics [74], subcellular and interaction proteomics [75][76][77][78] and identification of post-translational modification sites [79,80]. Even though SILAC represents a robust labelling strategy, the existing algorithms of SILAC-dependent MS data analysis are incapable of handling complex data sets.…”
Section: Label-based Mass Spectrometrymentioning
confidence: 99%
“…To establish the threshold ratios for determining the significantly changed proteins, we calculated the standard scores (z-scores) for protein ratios as previously described (18,19). Our analysis showed that at a 95% confidence level, those proteins with expression ratios greater than 1.22 or less than 0.73 could be considered significantly changed (20). To be stringent, however, we considered a protein as significantly altered only if its differential expression ratio ( S G treated/control) was greater than 1.5 or less than 0.67.…”
Section: Lc-ms/ms For Protein Identification Andmentioning
confidence: 99%
“…A "lock mass" approach [50] was used to obtain 1-3 ppm mass accuracies of the proteins and sequencing was performed via MS 3 in the linear trap with fragments detected in the Orbitrap. This group has further shown that quantification of proteins labeled by stable isotope labeling by amino acids in cell culture can also be achieved in the Orbitrap [51]. The SILAC labeled proteins also improved protein identification from CID fragmentation by providing information about the number of labeled residues in the fragments.…”
Section: Top Down Mass Spectrometry Instrumentation and Techniquesmentioning
confidence: 99%